Fincen requires financial institutions to obtain beneficial ownership information for legal entity customers. Issue 4 (7th November 2016) - Sandoval, Ignacio; Horn, Charles; Hall, Melissa
Abstract : Purpose: To provide an overview of the legal entity customer due diligence rule recently adopted by the Financial Crimes Enforcement Network (FinCEN), a bureau of the US Department of the Treasury. Design/methodology/approach: This paper provides an overview of the requirements of the legal entity customer due diligence rule as well as some observations regarding the scope of the rule, its interplay with other regulatory requirements, and some of the rule's ambiguities. Findings: While the preamble to the new rule suggests that FinCEN was attempting to accommodate industry concerns, the literal terms of the rule may have the opposite effect. Practical implications: Although financial institutions will have until May 2018 to come into compliance with the rule's requirements, they should begin developing the infrastructure to support compliance with the rule as soon as possible. Originality/value: Practical insights into issues that financial institutions may encounter when implementing the rule's requirements from experienced financial services lawyers.